The Effectiveness of Virgin Coconut Oil and Extra Virgin Olive Oil on Weight Gain in Malnourished Rats - Syahputra, M. Revanza Royhan Dany; Bamahry, Aryanti R.; Yanti, Andi Kartini Eka; Nurmadilla, Nesyana; Karim, Marzelina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Malnutrition is characterized by inadequate food intake, posing significant health risks, especially in vulnerable populations such as children and adolescents. This study aimed to evaluate the effects of virgin coconut oil (VCO) and extra virgin olive oil (EVOO) on weight gain in malnourished white rats (Rattus norvegicus). This study used post-test only with control group design, with 24 male rats divided into four groups: negative control, VCO, EVOO, and VCO & EVOO combination. Treatment was given for 14 days, with weight measurements taken at baseline, day 7, and day 14. The results showed a significant increase in body weight in all treatment groups (p <0.05). Although no significant difference was observed between the VCO and EVOO groups, a trend of greater weight gain was noted in the EVOO group. As conclusion, these findings indicate that VCO and EVOO can contribute to weight gain in white rats, although the effect is not significant. Further research is recommended to conduct long-term studies and include assessment of lipid profiles, glucose levels, and insulin to gain a deeper understanding of the effects of these oils.Keywords: virgin coconut oil; extra virgin olive oil; body weight; Rattus norvegicus